Five new species of the spider genus Clubiona Latreille (Araneae: Clubionidae) from Thailand - Pakawin Dankittipakul (2018)
Examination of a collection of the spider genus Clubiona Latreille, 1804 from northern and northeastern Thailand results in recognition of seven species, six of which belong to the japonica-group. Two new records in Thailand are added here (C. melanosticta Thorell, 1890 and C. filicata O. P.-Cambridge, 1874) and five species are new to science (C. campylacantha sp. n., C. octoginta sp. n., C. filifera sp. n., C. suthepica sp. n., C. abnormis sp. n.). Consequently, a total of twelve Clubiona species are hitherto known to occur in the kingdom. Special characters of the female genitalia of the japonica-group are investigated and their significance in taxonomic placement is discussed. The presently recognized species treated here are probably only a fraction of the actual Thai fauna. Copyright © 2008 Magnolia Press.